Smoking Habit at Home and Upper Respiratory Infection in Infants Aged 6-12 Months - Rustam, Musfardi; Sembiring, Nur Pelita; Effendy, Taswir (UI Scholars Hub, 2024)
Upper Respiratory Tract Infection (URI) is an acute infection caused by viruses, fungi, and bacteria. Smoking habit at home is a risk factor for URI in infants. This study aimed to determine a relationship between smoking at home and the incidence of URI in infants. This study was conducted the fourth week of February 2010 until the third week of April 2010 in Kampar District, Indonesia. This analytical study used a case-control design and cluster random sampling. The samples comprised 162 cases and 162 controls, infants aged 6-12 months. The cases were 162 infants aged 6-12 months suffering from URI within the last month. The controls included mothers visiting primary health care with infants aged 6-12 months and not suffering from URI within the last month. Data analysis took a logistic regression. This study showed that smoking habit at home had an Odds Ratio of 2.68 times (95%CI: 1.51-4.81) for experiencing URI compared to infants whose families did not have such habit. Health promotion of the dangers of smoking at home through a family approach and anti-smoking campaigns must be more intensively carried out among all Indonesian families to control URI.